ADJUSTING EMOTIONS/LINGUISTIC ADAPTATION: CINEMATIC MULTI-PERSPECTIVES ON THE HOURS - Corrizzato, Sara; Goracci, Giada (European Scientific Journal, ESJ, 2014)
As the terms themselves suggest, linguistics is the study of the human language, literary criticism includes the evaluation and the interpretation of literary texts and film studies foster the critical analysis of films and TV shows. Since written texts and audiovisual products are considered the mirror of the society to which they belong, the relevance of the three disciplines as possible analytical approaches to decode and understand society both anthropologically and culturally, is fully acknowledged in the academic world. Abandoning the conventional idea according to which linguists, literary and film critics have to work in separate environments, however, can promote a fertile intellectual dimension, in which a multi-leveled approach of analysis can be developed: film adaptations of literary texts, for instance, can encourage several eye-opening interpretations. The present paper analyses Michael Cunningham’s novel The Hours and Virginia Woolf’s masterpiece Mrs Dalloway as examples of multi-perspective texts. While not exhaustive, the study fosters a cross-cultural approach to film adaptation especially focusing on emotions and the way they can be transported into cinematic representation.